2022
DOI: 10.3390/jcm11102798
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Stroke Imaging Using a New Prototype of Low-Field MRI: A Prospective Direct 0.55 T/1.5 T Scanner Comparison

Abstract: Objectives: Ischemic stroke is a leading cause of mortality and acquired disability worldwide and thus plays an enormous health-economic role. Imaging of choice is computed-tomographic (CT) or magnetic resonance imaging (MRI), especially diffusion-weighted (DW) sequences. However, MR imaging is associated with high costs and therefore has a limited availability leading to low-field-MRI techniques increasingly coming into focus. Thus, the aim of our study was to assess the potential of stroke imaging with low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Alternatively, mid-field systems could facilitate deployment of MRI to good effect for general purpose radiology imaging in lower-resource regions and outpatient settings where 1.5T or 3T systems are scarce, as long as suitable diagnostic information can be gleaned. 83 Additionally, these systems offer advantages in niche applications, such as imaging high-susceptibility anatomy (e.g., lung and bowel), imaging near metallic implanted devices, or performing MRI-guided interventions. 70 Furthermore, the lower cost of these systems may encourage the adoption of applications that are difficult to justify, economically, with current high field system -for example, cardiac imaging may be achievable at mid-field, and is currently underutilized at ≥1.5T due to cost and complexity, despite clinical evidence of its diagnostic and prognostic value.…”
Section: Selection Of Appropriate Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, mid-field systems could facilitate deployment of MRI to good effect for general purpose radiology imaging in lower-resource regions and outpatient settings where 1.5T or 3T systems are scarce, as long as suitable diagnostic information can be gleaned. 83 Additionally, these systems offer advantages in niche applications, such as imaging high-susceptibility anatomy (e.g., lung and bowel), imaging near metallic implanted devices, or performing MRI-guided interventions. 70 Furthermore, the lower cost of these systems may encourage the adoption of applications that are difficult to justify, economically, with current high field system -for example, cardiac imaging may be achievable at mid-field, and is currently underutilized at ≥1.5T due to cost and complexity, despite clinical evidence of its diagnostic and prognostic value.…”
Section: Selection Of Appropriate Clinical Applicationsmentioning
confidence: 99%
“…Mid‐field system may be acquired at a lower cost and then can allow conventional ≥1.5T clinical MRI systems to be used when they are necessary, enabling departments to complete more MRI exams at an overall lower cost. Alternatively, mid‐field systems could facilitate deployment of MRI to good effect for general purpose radiology imaging in lower‐resource regions and outpatient settings where 1.5T or 3T systems are scarce, as long as suitable diagnostic information can be gleaned 83 . Additionally, these systems offer advantages in niche applications, such as imaging high‐susceptibility anatomy (e.g., lung and bowel), imaging near metallic implanted devices, or performing MRI‐guided interventions 70 .…”
Section: Key Themesmentioning
confidence: 99%
“…Pogarell et al reported excellent‐quality musculoskeletal images of knee and hip with metallic implant at 0.55 T 18 . Finally, Rusche et al showed that the 0.55 T MRI system may be deployed for imaging of stroke patients, demonstrating image quality comparable with that at 1.5 T 19 …”
Section: Introductionmentioning
confidence: 99%
“…16 In a case report by Breit et al images collected at 0.55 T demonstrated improved quality in postoperative thoracic spine in comparison with 3 T MRI, with substantially reduced metal artifacts. 17 Pogarell et al reported excellent-quality musculoskeletal images of knee and hip with metallic implant at 0.55 T. 18 Finally, Rusche et al showed that the 0.55 T MRI system may be deployed for imaging of stroke patients, demonstrating image quality comparable with that at 1.5 T. 19 However, the general utility of 0.55 T systems for routine brain imaging has not yet been assessed. In order for 0.55 T MRI scanners to be incorporated into healthcare systems, they must offer a high level of diagnostic certainty despite their potential disadvantages, such as reduced SNR compared with higher-field systems.…”
mentioning
confidence: 99%
“…At the same time, steps are being taken toward popularizing the use of magnetic resonance (MR) imaging for stroke. New evidence suggests that low-field MR imaging can offer a feasible alternative to its expensive 1.5-T counterparts, thus making MR imaging available to a broader spectrum of healthcare systems and, subsequently, patients [ 10 , 11 ].…”
mentioning
confidence: 99%